Linguistic innovation in feminist utopian fiction - Deirdre Burton (Ilha do Desterro)
In this paper I shall be discussing some recent feminist utopian novels and some of the more interesting implications and questions we might draw from a close study of the linguistic innovations in them. Consistently, we find that defamiliarisation of the language of the idealised world is a recurrent characteristic. I shall begin by describing four of these texts to you, in general. I shall go on to map out the types of defamiliarisation they offer the reader, linking this with the Sapir -Whorl hypothesis which asserts, in its strongest form, a determining connection between a culture's language, its thought and its reality. The implications and questions I want to draw from these comparisons are two-fold. The first is socio -linguistic and concerns real life issues of whether linguistic change is a necessary part of conceptual change.